2005
DOI: 10.2133/dmpk.20.227
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability in Nicotine Metabolism: C-Oxidation and Glucuronidation

Abstract: Summary: Nicotine has roles in the addiction to smoking, replacement therapy for smoking cessation, as a potential medication for several diseases such as Parkinson's disease, Alzheimer's disease, and ulcerative colitis. The absorbed nicotine is rapidly and extensively metabolized and eliminated to urine. A major pathway of nicotine metabolism is C-oxidation to cotinine, which is catalyzed by CYP2A6 in human livers. Cotinine is subsequently metabolized to trans-3?-hydroxycotinine by CYP2A6. Nicotine and cotini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 45 publications
1
68
1
3
Order By: Relevance
“…Two CYP2A6 alleles (CYP2A6*1 (wild type allele) and CYP2A6*4 were identified in the Javanese subjects used in the study. The selection of variant alleles for genotyping was based on functional importance and occurance frequency in Asian (Nakajima and Yokoi, 2005;Oscarson, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two CYP2A6 alleles (CYP2A6*1 (wild type allele) and CYP2A6*4 were identified in the Javanese subjects used in the study. The selection of variant alleles for genotyping was based on functional importance and occurance frequency in Asian (Nakajima and Yokoi, 2005;Oscarson, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…There are 80 numbered CYP2A6 allelic variants identified to date, however, not all have been functionally characterized (www.cypalleles.ki.se/cyp2a6.htm). Among 80 CYP2A6 allelic variants, CYP2A6*4 presents a whole gene deletion (Oscarson et al, 1999), that accounts for the majority of poor metabolizer (PM) in Asian populations (Nakajima and Yokoi, 2005;Oscarson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The mean K m (2.78 mM) and V max (297 pmol/mg.min) values for human liver microsomal cotinine N-glucuronidation determined in this study tended to be higher and lower, respectively, than previously reported values. The reasons for this are unclear, although 89-fold variability in the rates of nicotine N-glucuronidation has been observed in a panel of microsomes from 14 livers (Nakajima and Yokoi, 2005). The commercially sourced HLM employed in this study were a pool from 150 donors (equal numbers of males and females), whereas most reports have generally used microsomes from fewer donors (Ghosheh and Hawes, 2002;Nakajima et al, 2002;Kaivosaari et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…173 CYP2A6 is located on chromosome 19 (19q13.2) and a nearby region was associated with smoking frequency (X1 cigarette per day) in a genome-wide linkage scan. 39 Large interindividual and interethnic variations in CYP2A6 activity have been reported; [170][171][172][174][175][176][177] this variability is mainly attributed to the large genetic variations in CYP2A6. 178,179 A brief summary of how genetic variations in CYP2A6 affect smoking behaviors will be provided here as a detailed review was recently published.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%